Study on New Strategies for the Future Marketing of Zhuhai Island Tourism based on Qi’ao Island - Chen, Longjuan; Zheng, Canbin; Chen, Senning; Zhang, Miao (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of tourism, island tourism has gradually become an important travel option. In this paper, the island "Qi’ao Island" in Zhuhai City is selected as a research case, and a systematic and scientific investigation and analysis is carried out from the perspective of tourists’ experience, taking into account various aspects of the Zhuhai island tourism market, such as demand, supply, competition, consumer behaviour, marketing methods, etc. This aims to formulate a reasonable solution for the tourism enterprises. This aims to provide a basis for tourism enterprises to formulate reasonable marketing strategies and to provide general guiding principles and directions for the future island tourism market in Zhuhai. The data analysis method covers descriptive statistics and cross-analysis of basic tourist information in order to develop more precise marketing strategies. The results of the study indicate the following: firstly, young people are the main audience of Zhuhai’s island tourism market, and they show a strong interest in and demand for island tourism. Second, although tourists’ satisfaction with the scenic spots on Qiaodao Island is high, there is still room for improvement, especially in terms of infrastructure, transport convenience, and environmental hygiene. Thirdly, there is a diversified trend of users’ attention, focusing not only on the natural scenery and history and culture of the island, but also on recreational activities and special cuisines. Fourth, the price level affects the purchasing power of tourists to a certain extent, and too high or too low prices may affect tourists’ willingness to spend and satisfaction. Fifth, high-quality service can enhance tourists’ satisfaction and increase the repeat rate, service attitude, efficiency and content are important factors of service quality. Finally, the development of island tourism is not only limited to play and sightseeing, but can also achieve wider development through integration and innovation with other industries, such as fishery, agriculture and industry. Based on the above conclusions, in order to further enhance the popularity and brand value of Zhuhai’s islands, this paper puts forward the following suggestions: firstly, Zhuhai should strengthen the planning and guidance, optimise the industrial layout, improve the quality of tourism, strengthen the environmental governance, and improve the competitiveness of the market, so as to create a new highlight of Zhuhai’s marine economy. Specifically, it can rely on the natural resources and history and culture of Qi’ao Island to create a unique tourism brand and develop diversified tourism products and services to meet the needs of different levels and types of tourists. Secondly, it can make use of online media and social platforms for publicity and promotion to enhance the popularity and reputation of Qi’ao Island, and establish co-operative relationships with other islands and tourism organisations to form complementary advantages and win-win situations, etc.